2012
DOI: 10.1002/adfm.201201913
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Absorbing Star‐Shaped Small Molecules for the Preparation of Ternary Cascade Energy Structures in Organic Photovoltaic Cells

Abstract: Two anthracene‐based star‐shaped conjugated small molecules, 5′,5″‐(9,10‐bis((4‐hexylphenyl)ethynyl)anthracene‐2,6‐diyl)bis(5‐hexyl‐2,2′‐bithiophene), HBantHBT, and 5′,5″‐(9,10‐bis(phenylethynyl)anthracene‐2,6‐diyl)bis(5‐hexyl‐2,2′‐bithiophene), BantHBT, are used as electron‐cascade donor materials by incorporating them into organic photovoltaic cells prepared using a poly((5,5‐E‐alpha‐((2‐thienyl)methylene)‐2‐thiopheneacetonitrile)‐alt‐2,6‐[(1,5‐didecyloxy)naphthalene])) (PBTADN):[6,6]‐phenyl‐C71‐butyric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(82 citation statements)
references
References 51 publications
2
80
0
Order By: Relevance
“…The current approaches for cell architecture improvement include the use of a mix solvent for interfacial morphology control, the incorporation of additives that obtain proper molecular orientation, the formation of a cascade energy structure to cover more solar spectra with ternary blend, and the addition of metal nanostructures to enhance absorption via the excited surface plasmon. These cell architecture methods have mainly been investigated for complementary absorption and better utilization of the solar radiation spectrum, particularly for improving the short-circuit current density (J sc ) of the BHJ solar cells [15][16][17][18][19][20]. However, the correlation between dopant and consequent V oc enhancement is still ambiguous and rarely discussed.…”
Section: Introductionmentioning
confidence: 98%
“…The current approaches for cell architecture improvement include the use of a mix solvent for interfacial morphology control, the incorporation of additives that obtain proper molecular orientation, the formation of a cascade energy structure to cover more solar spectra with ternary blend, and the addition of metal nanostructures to enhance absorption via the excited surface plasmon. These cell architecture methods have mainly been investigated for complementary absorption and better utilization of the solar radiation spectrum, particularly for improving the short-circuit current density (J sc ) of the BHJ solar cells [15][16][17][18][19][20]. However, the correlation between dopant and consequent V oc enhancement is still ambiguous and rarely discussed.…”
Section: Introductionmentioning
confidence: 98%
“…The cascade like energy levels (shown in Fig. 4) of ternary blend PSCs can facilitate charge transfer at the D/A interface owing to the bridging effect to reduce the energy loss [31,32]. For example, Huang et al [33] reported that by incorporating a small molecule donor 7,7'-{5,5'- [10,12-…”
Section: More Efficient Charge Transfer and Charge Transportmentioning
confidence: 99%
“…Cha et al [31] developed a naphthalene derivative polymer donor material, PBTADN, and the acceptor material, PC 71 BM, were blended with either of two different anthracene-based star-shaped conjugated small molecules, HBantHBT and BantHBT, which provided intermediate energy levels to produce a ternary cascade energy structure. The cascade structure effects of the star-shaped conjugated small molecules were examined in a P3HT:PC 61 BM blend system.…”
Section: Two Donors and One Acceptor (D 1 -D 2 -A) Systemmentioning
confidence: 99%
“…Among these additives, the fullerene derivatives take the majority due to its compatibility with host acceptors as well as the established solvent systems, though there were other small molecules that revealed a similar function [53][54][55]. Herein we focus on the development of a variety of kinds of fullerene derivatives as morphological control agents.…”
Section: Small Moleculesmentioning
confidence: 99%